TEPUNG GADUNG (Dioscorea Hispida DENNST) BEBAS SIANIDA DENGAN MERENDAM PARUTAN UMBI DALAM LARUTAN GARAM - Muljo Hardjo (LPPM Universitas Terbuka, 2005)
The objection of the research is to study the effect of soaking time if sredded of gadung (Dioscorea hispida Dennst) soaking in brine. The research design comprises of two factorials. Those are consentration of brine 5% and 7,5% and soaking time comprises three levels 48 hours, 60 hours, and 72 hours, The research shows that soaking time 72 hours with brine 5% and 7,5% was the safest gadung flour to be consumed. The treatment of soaking time 72 hours in 7,5% brine has 18,75 ppm HCN, 41,51% starch, 1,59% fiber, 10,8% water, 6,01% ash, 97,84 color degree and preference taste of tiwul 2,1 betweendislike and like. The treatment of soaking time 72 hours in 5% brine has 19,62 ppm HCN, 50,49% starch, 1,58% fiber, 9,64% water, 4,34% ash , 98,41 color degree, and preference taste of tiwul 2,87 between dislike and like.